Rural Transformation: The challenge of Sustainable Agriculture, Environmental Pollution, Urban-Rural Income Inequality and Ageing Rural Population - Lee, John_CG; Sukoharsono, Eko Ganis (Journal of Environmental Accounting and Management, 2026)
In recent time China rural sector has made remarkable achievements but is facing major new challenges. As a signatory of the UN SDG's and the Paris Climate Accord, China is committed to sustainable agricultural practices and achieving net zero carbon emission by 2050. The four new sets of challenges are 1) sustainable agriculture, 2) environmental pollution, 3) urban-rural income inequality, 4) depopulation and underdevelopment of the rural region. This study aims to explore and analyses the rural transformation processes in the case of Jilin province, North-East China with respect of these four challenges. A qualitative approach was adopted, involving focus group discussions (FGD) and the data is derived from thirty-two participants recruited then divided into two groups of equal number for separate FGD and thematic analysis to examine the data. The results of the study are, in the context of sustainable agriculture and environmental pol-lution, current farming practices are traditional, highly prone to diseases outbreak, polluting the soil and waterway. Income gap remains significant as measured by the urban-rural income ratio but has been decreasing since 2013.This study finds whilst past and present government policies and ef-forts have improved farm incomes, agricultural production and rural living, it has not reversed the mass migration of the young and able-bodies to the urban and thus the rural remain hollowed out. On a case-to-case basis, the finding of this study is generalizable for policymakers and stakeholders facing identical or similar challenges. [1,2]